Sock puppets: How the government lobbies itself and why - Christopher Snowdon (Institute of Economic Affairs (IEA), 2012)
It's time for a radical overhaul of state-funded charitiesNew research, released today, reveals the true extent of government funded lobbying by charities and pressure groups.This report argues that, when government funds the lobbying of itself, it is subverting democracy and debasing the concept of charity. It is also an unnecessary and wasteful use of taxpayers' money. By skewing the public debate and political process in this way, genuine civil society is being cold-shouldered.Sock Puppets: How the government lobbies itself and why, by Christopher Snowdon, shows that:In the last 15 years, state funding of charities in Britain has increased significantly. 27,000 charities are now dependent on the government for more than 75 per cent of their income and the 'voluntary sector' receives more money from the state than it receives in voluntary donations.State funding weakens the independence of charities, making them less inclined to criticise government policy. This can create a 'sock puppet' version of civil society giving the illusion of grassroots support for new legislation. These state-funded activists engage in direct lobbying (of politicians) and indirect lobbying (of the public) using taxpayers' money, thereby blurring the distinction between public and private action.State-funded charities and NGOs usually campaign for causes which do not enjoy widespread support amongst the general public (e.g. foreign aid, temperance, identity politics). They typically lobby for bigger government, higher taxes, greater regulation and the creation of new agencies to oversee and enforce new laws. In many cases, they call for increased funding for themselves and their associated departments.Urgent action should be taken, including banning government departments from using taxpayer's money to engage in advertising campaigns, the abolition of unrestricted grants to charities and the creation of a new category of non-profit organisation, for organisations which receive substantial funds from statutory sources.
Keywords: 330; Interest politics; Political decision-making; Non-profit organization; New political economy; EU states; Interessenpolitik; Politische Willensbildung; Gemeinnützige Organisation; Neue politische Ökonomie; EU-Staaten